The vitamin D metabolome: An update on analysis and function - Jenkinson, Carl (Cell biochemistry and function, 2019)
Current understanding of vitamin D tends to be focussed on the measurement of the major circulating form 25‐hydroxyvitamin D3 (25OHD3) and its conversion to the active hormonal form, 1α,25‐dihydroxyvitamin D3 (1α,25(OH)2D3) via the enzyme 25‐hydroxyvitamin D‐1α‐hydroxylase (CYP27B1). However, whilst these metabolites form the endocrine backbone of vitamin D physiology, it is important to recognise that there are other metabolic and catabolic pathways that are now recognised as being crucially important to vitamin D function. These pathways include C3‐epimerization, CYP24A1 hydroxylase, CYP11A1 alternative metabolism of vitamin D3, and phase II metabolism. Endogenous metabolites beyond 25OHD3 are usually present at low endogenous levels and may only be functional in specific target tissues rather than in the general circulation. However, the technologies available to measure these metabolites have also improved, so that measurement of alternative vitamin D metabolic pathways may become more routine in the near future. The aim of this review is to provide a comprehensive overview of the various pathways of vitamin D metabolism, as well as describe the analytical techniques currently available to measure these vitamin D metabolites.